Physical activity and exercise as precursors of wellbeing of menopausal women in the community (2024)
Ageing or menopausal women do come up with variety of physical, psychological and social health related challenges in various community settings including educational institutions. This paper examined the impact of physical activity and exercise as a tool for the wellbeing of ageing and menopausal women in the community which they can use to manage or cope with their health related conditions at midlife period. Physical activity or exercise have been viewed by many experts as a coping menopausal coping strategy against various symptoms, women experience during the period that affect their quality of life